THE CHARACTERIZATION AND FANTASY IN THE FAIRY TALE OF THE TWO SISTERS AND BAWANG MERAH BAWANG PUTIH - Siti Nurhasanah; Pepen Priyawan; Erfan Muhammad Fauzi (Wiralodra English Journal, 2025)
The purpose of this study is to conduct a comparative analysis in which the data is analyzed descriptively and qualitatively by using structural analysis theory. This research analyses the main characters in two fairy tales, The Two Sisters from England and Bawang Merah Bawang Putih from Indonesia. The results of this study aim to explore: 1) the similarities and  differences between the main characters in The Two Sisters and Bawang Merah Bawang Putih, and 2) how the characters are portrayed through structural analysis. The results of this study show that there are similarities in the characters of the two fairy tales. Bawang Putih is described as a hardworking character, identical to one of the sisters in The Two Sisters fairy tale who is also described as such. Bawang Merah, is portrayed as jealous and lazy, similar to his sister, who is also not a good character. Both stories also show similarities in using the contrast between good and bad characters. This research also contributes significantly to the field of comparative literature by showing how comparative methods and structural analysis theory can be applied to explore similarities and differences in fairy tales from different cultural backgrounds.